Long-term outcomes of Wagner self-locking stem with bone allograft for Paprosky type II and III bone defects in revision total hip arthroplasty: A mean 15.7-year follow-up - Junting Zang (Journal of Orthopaedic Surgery, 2019)
Purpose: Massive bone defects represent a challenge in revision total hip arthroplasty (THA). Wagner self-locking (SL) stem is a favorable option for this technique; however, its long-term outcomes with bone allograft have rarely been reported. The purpose of this study was to investigate the long-term outcomes of this stem with bone allograft for Paprosky type II and III bone defects in revision THA. Methods: A total of 38 patients (40 hips) who underwent revision THA with the Wagner SL stem were retrospectively reviewed. Bone allograft was placed in every patient. Clinical outcomes were determined using the Japanese Orthopedic Association’s hip scoring system (JOA hip score). Stem subsidence, stem fixation, and remodeling of the grafted bone were assessed radiographically. The survival rate of the stem was assessed by Kaplan–Meier survival analysis. Results: The mean JOA hip score at the latest follow-up was 75.3 points. Stem subsidence of ≥10 mm was observed in four hips (10.0%). Moreover, 67.5% (27/40) of hips were stable, and 27.5% (11/40) had fibrous fixation. Bone restoration was observed in 25 hips (62.5%). At a mean follow-up of 15.7 years, the cumulative stem survival rates were 96.6%and 91.7% with “stem re-revision for loosening” and “stem re-revision for any reason” as the end points, respectively. Conclusion: The Wagner SL stem with bone allograft for proximal femoral bone defects in revision THA is a clinically beneficial procedure.